Evaluation of the symptoms and treatment prescribed to hospitalized patients - Roldi,Mariana da Silva (2016)
Summary Objective: Evaluation of the presence of symptoms and suitability in the treatment of patients admitted to medical wards at HU-UFSC. Identification of patients eligible for palliative care (PC). Method: A prospective cohort study, which evaluated patients in the first 48 hours of hospitalization (D1) and after 48 hours (D2). On D1, palliative performance and symptom assessment scales were applied (PPS/ESAS). The treatment established for the control of detected symptoms was also identified. On D2, the ESAS scale was applied again, and the medical prescription reviewed. When the presence of severe symptoms was found, the attending physician was informed. Patients who presented PPS≤60 were eligible for PC prioritization. For statistical analysis Student’s t and χ2 tests were used. Results: 168 patients were studied. Of these, 26.8% had PPS≤60. PC was described in one medical chart. Patients with mild symptoms reported significant worsening in the second evaluation, especially worsening in pain (32.3%) and well-being (49.3%). Symptoms considered severe showed significant improvement. There was no control of pain reported as moderate. Prescriptions for pain control were predominantly “if necessary”, prevailing the use of non-opioid analgesics and weak opioids. The attending physician was informed of 116 (69%) patients with ESAS score≥4. Conclusion: The control of symptoms, especially those considered mild, was unsatisfactory. Drug prescription was inadequate to control pain, and non-existent for some reported symptoms. There was no adequate prioritization of PC. There is a need for optimization and dissemination of PC among health professionals.